2017
DOI: 10.1007/s00402-017-2645-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of locking plate versus hook plate osteosynthesis of Neer type IIB lateral clavicle fractures

Abstract: Both HPO and LPO were equally effective in relation to restoration of vertical stability, overall functional outcome and fracture consolidation in treatment of Neer IIB fractures. Contrary to our hypothesis, HPO was not associated with superior recreation of the coracoclavicular distance. Considerable drawbacks of HPO were an inferior ACJ-specific outcome (Taft-Score) and a higher overall complication rate. Level of evidence IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 31 publications
0
59
0
Order By: Relevance
“…2) the clavicle hook has been located in the subacromial area for a long time, which squeezes the space, and is prone to cause acromial impingement, acromial dropping bursitis, and even subacromial osteolysis. 3) Long-term placing of hook steel plate could cause complain of shoulder discomfort, which often requires surgical removal, and may lead to a certain degree of reduction loss of acromioclavicular joint after removal of the plate [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…2) the clavicle hook has been located in the subacromial area for a long time, which squeezes the space, and is prone to cause acromial impingement, acromial dropping bursitis, and even subacromial osteolysis. 3) Long-term placing of hook steel plate could cause complain of shoulder discomfort, which often requires surgical removal, and may lead to a certain degree of reduction loss of acromioclavicular joint after removal of the plate [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Hook plate xation has a good union rate. However, several complications, including acromial osteolysis, subacromial impingement, and ACJ arthrosis are observed after surgery [6,7,17]. Recently, coracoclavicular ligament reconstruction has achieved robust xation in a biomechanical study.…”
Section: Discussionmentioning
confidence: 99%
“…Locking plate xation is selected for patients with a relatively large lateral fragment because numerous screws cannot be inserted into a small fragment to achieve robust xation. Hook plate has a higher rate of complications, such as acromial osteolysis, subacromial impingement, and ACJ arthrosis, than locking plate osteosynthesis [6,7]. Although coracoclavicular ligament reconstruction can achieve a biomechanically strong xation, this procedure is technically demanding [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more individuals who underwent internal fixation with a distal clavicular locking plate were able to return to their previous work within 3 months after surgery and had fewer complications than those who underwent fixation with the clavicular hook plate. Erdle et al [22] found that the overall functional outcome was similar in the clavicle hook plate and distal clavicle locking plate groups. We performed a sensitivity analysis by sequentially omitting each study, and this analysis showed that our results type II distal clavicle fractures because these fractures tend to displace and are associated with a higher risk of nonunion compared with other clavicle fracture types.…”
Section: Relation To Other Systematic Reviewsmentioning
confidence: 96%